2015
DOI: 10.15344/2455-2356/2015/101
|View full text |Cite
|
Sign up to set email alerts
|

Should We Consider Bilirubin When Dosing Troponin in Newborns? Case Report

Abstract: Background: Troponin is a protein of the troponin-tropomyosin complex in myocardium and it is considered an highly sensitive marker of myocardial necrosis both in adults and newborns with perinatal asphyxia. Some studies assume that high troponin levels in adults without signs of myocardial necrosis could be conditioned by some factors, such as hemolysis, turbidity, and hyperbilirubinemia. Case presentation: We report a case of a term female newborn of Caucasian race, with high troponin levels in absence of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Giacchi et al reported a case of falsely high troponin I levels in a baby with jaundice. However, in our case, bilirubin levels had always been within the normal ranges and the baby never required phototherapy 16…”
Section: Discussionmentioning
confidence: 45%
“…Giacchi et al reported a case of falsely high troponin I levels in a baby with jaundice. However, in our case, bilirubin levels had always been within the normal ranges and the baby never required phototherapy 16…”
Section: Discussionmentioning
confidence: 45%